Hubungan antara Penggunaan Kontrasepsi Hormonal dengan Kejadian Hipertensi pada Wanita Usia Subur di Indonesia (Analisis Data Indonesian Family Life Survey 5) - Theni Yuniarti; Amrina Rosyada (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: The incidence of hypertension in women is 36.9%, allegedly related to hormonal changes triggered by the use of hormonal contraceptives. This study aims to analyze the relationship between the use of hormonal contraception on the incidence of hypertension in women of childbearing age. Methods: This cross-sectional study used IFLS 2014 data and involved 7,097 participants who were selected using multistage random sampling technique. The research variables included age, education, work status, physical activity, stress, use and length of time being a hormonal family planning acceptor, work status, blood pressure and obesity. Data analysis was carried out descriptively and analytically using logistic regression. Results: The incidence of hypertension reached 27.2%, and the multivariate analysis showed the significant correlation with age and duration of hormonal contraceptive use (p=0.000; PR=2.809; 95%-CI=2.516-3.136 and p=0.000; PR=1.002; 95% -CI=1.001-1.003). Conclusion: The incidence of hypertension in hormonal contraceptive users is related to age and period of use. Hormonal family planning acceptors need to regularly control blood pressure with age to monitor the incidence of hypertension.